Letter from Mary A. Post to James Curtis Booth, October 12, 1856 - Post, Mary A. (1856)
Mary A. Post, a cousin of James Curtis Booth (1810-1888), apologizes for lapse in their correspondence and relates her difficulties adjusting to her widowed state.
Keywords: Booth, James Curtis, 1810-1888